Exploring Cross-Professional Collaborations among Professional and Lay Mental Health Practitioners towards Schizophrenic Care in Ghana - Nkrumah, R. (University Of Ghana, 2017)
Ghana is grappling with inadequate professional mental health practitioners for the treatment of schizophrenia. Since many patients partly access the services of non-professional mental health practitioners, implementation of collaborative framework will potentially ensure effective and quality delivery of schizophrenic care. This study examined opinions about the different collaborative frameworks between professional and non-professional mental health practitioners for the delivery of schizophrenic care. Field research data was collected from three regions in Ghana using mixed research design. The survey involved 110 practitioners and the interviews involved 30 practitioners. The quantitative data was analysed using multivariate analysis of variance. The second study which is the qualitative part was analysed using thematic analysis. The findings showed that professional mental health practitioners show significantly more positive attitudes towards collaborative schizophrenic care than the non-professional mental health practitioners. Professional mental health practitioners experienced higher levels of stigma associated with schizophrenic care than non-professional mental health practitioners. Pastors had more positive or supportive attitudes towards patients with schizophrenia, compared to other non-professional mental health practitioners. The qualitative findings revealed that lay practitioners understanding of schizophrenia is marked by mainly the pattern of their symptoms. It was also observed that categorization of schizophrenia is still strongly held among the lay practitioners. The findings are discussed in relation to enhancing schizophrenic care and mental health in Ghana.
Thesis (MPhil.)
Keywords: CROSS-PROFESSIONAL; HEALTH PRACTITIONERS; SCHIZOPHRENIC CARE; Ghana